Rancang Bangun Dan Uji Kinerja Mesin Pencacah Rumput Gajah Untuk Pakan Ternak Dengan Menggunakan Pisau Tipe Reel (Construction Design and Test Performance of Elephant Grass for Cattle Feed using Reel Type Knife): Construction Design and Test Performance of Elephant Grass Cutting Machine for Cattle Feed using Reel Type Knife - Wahyu K. Sugandi; Asep Yusuf; Muhammad Saukat (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2016)
Elephant grasses demand for cattle feed in Lembang area is increasing in quantities, however qualities of the cutting grasses have not achieved the demand of cattle feed, i.e. length of some of cutting grasses found above 5cm. Therefore, research about elephant grasses cutting technology in order to achieve the standard of forages (cattle feed) production, i.e. 1-5 cm cutting grasses length, need to be conducted. Aimed of this research was to develop machine that could cut elephant grasses by using precision cutting mechanism on the required dimension (1-5 cm). Method used in this research was engineering method using step as follow: (1) Measurement of elephant grasses characteristic; (2) Design analysis of cutting machine, which covered design of the cutter knife, hopper design, frame and transmission system; (3) Construction of elephant grasses cutting machine; (4) Functional test of elephant grasses cutting machine; (5) Test performance of elephant grasses cutting machine; and (6) Measurement of the cutting grasses. Result showed that physical characteristic of elephant grasses were as follow: average length of grass leaves 99.4 cm, leaves wide 2.65 cm, leaves thickness 0.23 cm, and leaves weight 7.8 g. Machine dimension was 800 mm length, 750mm wide, and 104mm height. Power need to cut elephant grasses was 1.6 kW and machine capacity 1988 kg/hour. Length of the produced cutting grasses was 1-3 cm.